A 3-D FSI simulation for the performance prediction and valve dynamic analysis of a hermetic reciprocating compressor - Bacak, Aykut; Pinarbasi, Ali; Dalkilic, Ahmet Selim (ELSEVIER SCI LTD, 2023)
Hermetic reciprocating compressors consume the most electricity, and an improvement in compressor performance has a direct impact on compressor efficiency. Valve motion and pressure pulsation should be precisely predicted to assess the thermodynamic performance. In this paper, a three-dimensional fluid-structure interaction model validated by experiments is developed to investigate the oscillation motion of the suction and discharge reed valves, compression power, and mass flow rate of a hermetic reciprocating compressor operating under ASHRAE (54.4 degrees C/-23.3 degrees C) at the speed of 2100 rpm and additional specific refrigerator operating conditions such as (25 degrees C/-20 degrees C) and (40 degrees C/-25 degrees C) at the speeds of 1300 and 1600 rpms, respectively. Different from the others, no prior study has explored the whole compression cycle, including all four essential phases by showing the compressor's pV and valve oscillation diagrams under these operating conditions. In addition, the advanced mesh refinement method is computationally straightforward and has excellent numerical stability. Using this method as the third one in the literature, the mesh structure of complex geometries is generated without additional time or effort. Thus, the development of the model and the solution takes significantly less time than with other methods. When the obtained numerical outputs using the RNG k-epsilon turbulence model and experimental data are compared, the turbulence model is found to be reliable in the prediction of thermodynamic performance and valve lift. The deviations between experimental and numerical outcomes are 1.79%, -0.6%, and 3.44% for compression power and -1.28%, 0.6%, and 2.44% for mass flow rate regarding ASHRAE and additional operating conditions.
Keywords: Reciprocating compressor; Thermodynamic losses; pV indicator diagram; Reed valve motion; Fluid-solid interaction; Beam modeling; Compresseur alternatif; Pertes thermodynamiques; Diagramme des indicateurs p-V; Mouvement des soupapea` lamelles multiples; Interaction fluide-solide; Mode ' lisation en faisceau; LINEAR COMPRESSOR; SUCTION VALVE; FLOW; BEHAVIOR; MOTION; MODEL; Thermodynamics; Engineering